2019
DOI: 10.22492/ije.7.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Verbal Aptitudes as Predictors of Senior Secondary School Students’ Performance in Economics

Abstract: This study examined the predictive power of quantitative and verbal aptitudes on the performance of senior secondary school students in Economics. The study arose from the poor performance of students in the Senior School Certificate Examination and the General Certificate in Education Economics. The study adopted descriptive survey research design. Multistage sampling technique was employed in selecting a total of three hundred and thirty senior secondary two Economics students from ten schools comprising of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Accordingly, it is in line with an earlier conclusion drawn by The Understood Team (2017), which stated that remediation helps the low achievers to bridge the gap concerning what they should know and what they already know Feedback together with remediation can help economics students develop their skills in quantitative economics prior to external examinations as suggested by WAEC Chief Examiners in their reports. It then means that for an increased achievement in economics examinations conducted by WAEC, economics teachers should endeavor to administer feedback together with remediation in teaching, learning and evaluation of quantitative economics, since evaluation methods adopted by the teacher in the teaching and learning of quantitative economics is one of the factors for poor achievement in economics (Anazia, 2019;Chudi, 2013;Ugan, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it is in line with an earlier conclusion drawn by The Understood Team (2017), which stated that remediation helps the low achievers to bridge the gap concerning what they should know and what they already know Feedback together with remediation can help economics students develop their skills in quantitative economics prior to external examinations as suggested by WAEC Chief Examiners in their reports. It then means that for an increased achievement in economics examinations conducted by WAEC, economics teachers should endeavor to administer feedback together with remediation in teaching, learning and evaluation of quantitative economics, since evaluation methods adopted by the teacher in the teaching and learning of quantitative economics is one of the factors for poor achievement in economics (Anazia, 2019;Chudi, 2013;Ugan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As averred by Anazia (2019) and Ugan (2017), the poor achievement of students at WAEC causes a lot of curiosity to the general public as to the prospect of education in these West African countries. Different researchers (Adu et al, 2009;Chudi, 2013;Ugan, 2017) have identified so many factors as accountable for the low achievement of WAEC candidates particularly in economics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Giofrè, Donolato, & Mammarella, (2018) assumed that verbal tests are able to predict academic achievement. Similarly, Burton, Welsh, Kostin, VanEssen, & Service (2009) and Anazia (2019) showed that verbal tests are strong predictors of academic achievement.…”
Section: Discussionmentioning
confidence: 91%
“…According to Oyetunde [21], the items used in the aptitude test measure specific abilities such as verbal and numerical abilities to predict academic performance in educational programs. Verbal and numerical abilities are also predictors of student performance, namely learning outcomes in the field of economics for junior high school students [28].…”
Section: Issn: 2252-8822 mentioning
confidence: 99%